2021
DOI: 10.5454/mi.15.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Phytochemical Characteristics of Crude Extract of Jasmine Flower Against Escherichia coli and Staphylococcus aureus

Abstract: Indonesia is a famous country had the diversity of plants, especially agricultural product and herbs, they had a potential of antimicrobial as a like Jasmine Flower (Jasminum sambac Ait). This study Indonesia is a famous country had the diversity of plants, especially agricultural product and herbs, they had a potential of antimicrobial as a like Jasmine Flower (Jasminum sambac Ait). This study aimed to determine the phytochemical and antimicrobial activity of jasmine flower. Extraction was done by maceration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Common microorganisms such as Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) were investigated using the MIC method. MIC values from different studies and different extraction methods were reported differently [ 34 , 35 , 36 , 37 ]. However, it can be concluded that jasmine essential oil from HFC-134a extraction also has antimicrobial potential, as indicated by other previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Common microorganisms such as Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) were investigated using the MIC method. MIC values from different studies and different extraction methods were reported differently [ 34 , 35 , 36 , 37 ]. However, it can be concluded that jasmine essential oil from HFC-134a extraction also has antimicrobial potential, as indicated by other previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was found that essential oils can cause a leakage of ions and cell contents from bacteria [ 8 ] and are highly effective against Gram-positive bacteria over Gram-negative bacteria, similar to another experimental study on inhibition zones [ 43 ]. It was also reported that Gram-negative bacteria are covered by a lipopolysaccharide layer that helps protect these bacteria from antibacterial substances [ 44 ]. In this study, the Robusta roasted coffee extracts could perform as antibacterial substances against Gram-positive bacteria better than Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%